ChemInform Abstract: Na0.5Ce0.5MoO4 as a New Light Absorption Material to Efficiently Degrade RhB under Visible Light Irradiation. Issue 34 (4th August 2016) - Yang, Liming; Teng, Fei; Xu, Juan; Yang, Yang; Kan, Yandong; Gu, Wenhao
Abstract: Na0.5 Ce0.5 MoO4 is prepared by hydrothermal reaction of Na2 MoO4 and Ce(NO3 )3 in the presence of excess (H2 N)2 CS (autoclave, 180 °C, 2 d).